Sea toll route optimization with artificial bee colony algorithm on capacitated vehicle routing problem - Gunawan (BKS-TM Indonesia, 2025)
Maritime transportation plays a crucial role in inter-island logistics distribution in Indonesia, one of which is through the Sea Toll Road program. Despite its economic benefits, the shipping sector also contributes to environmental pollution due to the high consumption of fossil fuels and the resulting pollutant emissions. The implementation of a carbon tax is one effort to reduce fuel consumption by increasing the burden of ship operational costs. As the Sea Toll route expands every year, this study was conducted to evaluate and optimize shipping routes to be more technically efficient and environmentally friendly. The research focused on 7 Sea Toll routes departing from Tanjung Perak Port, Surabaya, by solving the Capacitated Vehicle Routing Problem (CVRP) using the Artificial Bee Colony (ABC) algorithm, an optimization algorithm inspired by the behavior of honeybees in foraging. The results showed a decrease in total distance traveled from 16,708 NM to 13,816 NM, an increase in average load capacity from 67.86% to 95%, and a decrease in carbon tax costs by 17.3%. The research results prove that the ABC algorithm is effective in designing optimal shipping routes in terms of route efficiency, load distribution, operational costs, and environmental sustainability.